The Effectiveness of Online Services at The Population and Civil Registration Services of Pekanbaru City - Abid Arrijal; Dadang Mashur (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2021)
The online service carried out at the Dukcapil Office of Pekanbaru City has the aim of creating an effective public service process so that it can make the service process fast, easy, cheap, and uncomplicated. There are two kinds of online services, namely Sipenresiden in the form of a website and Waiting Service (LAGU) which is an application. In this online service process, there are several factors that become obstacles in the effort to realize effective services, namely the lack of awareness of the Dukcapil service to the people of Pekanbaru City who take care of population administration, the lack of readiness of facilities and infrastructure and human resources owned by the Department, as well as socialization about online services to the public. less active society. This study has a purpose, namely to determine the effectiveness of online services carried out by the Department of Population and Civil Registration of Pekanbaru City. The theoretical concept used is the theory of effectiveness by Mahmudi 2019. By using qualitative research methods and data collection based on interviews, observations and documentation. The results of the research that the author can get are that the implementation of online services still has several factors that become obstacles experienced by the Pekanbaru City Population and Civil Registration Office, so that the online services implemented have not been effective.